(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article analyzes the reforms carried out in the field of higher education of Uzbekistan, in particular the Kashkadarya region on the basis of statistical data. It sets out the main goal of training qualified specialists in accordance with modern requirements and bringing the quality of education to the international level. The need to develop and implement strategic measures to improve the quality of the educational process, further increase the scientific and potential level of professors and students and introduce an individual approach to students is highlighted.